2018
DOI: 10.30742/jikw.v5i2.337
|View full text |Cite
|
Sign up to set email alerts
|

Induction of interleukin-6 trigger an apoptosis through IL-17 and stat3 pathway that alleviated by phycocyanin treatment

Abstract: AbstrakPenelitian ini bertujuan untuk menganalisis dosis optimal induksi IL-6 pada tikus hamil yang dapat memicu peningkatan tekanan arteri dan protein sebagai dua gejala preeklampsia. Sebanyak 25 tikus hamil dibagi menjadi 5 kelompok, yaitu tikus hamil kelompok kontrol (tanpa induksi IL-6), 1 kelompok tikus hamil diberi induksi IL-6 dalam dosis 1,25 ng / hari, 1 kelompok tikus hamil diberi induksi IL-6 dosis 2,5 ng/ hari, 1 kelompok tikus hamil diberi induksi IL-6 dosis 5 ng / hari, dan kelompok tikus hamil d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…However, parallel analysis (Table 4) showed that the expression level of the IL-17 decreased with ENPC (1000 µg.mL − 1 ). This result is consistent with Haryanti & Gondo (2018), where increasing the dose of phycocyanin inhibited apoptosis by suppressing IL-17.…”
Section: Discussionsupporting
confidence: 91%
“…However, parallel analysis (Table 4) showed that the expression level of the IL-17 decreased with ENPC (1000 µg.mL − 1 ). This result is consistent with Haryanti & Gondo (2018), where increasing the dose of phycocyanin inhibited apoptosis by suppressing IL-17.…”
Section: Discussionsupporting
confidence: 91%